An integrated analysis framework for water resources sustainability considering fairness and decoupling based on the water resources ecological footprint model: A case study of Xinjiang, China. (10th January 2023) - Li, Donglin; Zuo, Qiting; Jiang, Long; Wu, Qingsong
Abstract: One of the critical barriers to water resources sustainability (WRS) is the poor understanding of water scarcity, and the water resources ecological footprint (WEF) has become an important tool for assessing WRS due to its insight into the water shortage crisis. In this study, an integrated diagnostic framework was developed by combining the three-dimensional water resources ecological footprint (3D WEF) model and the Gini coefficient approach as well as the decoupling effort model to comprehensively analyze WRS. It can not only fully reveal water shortages from three dimensions of water resources ecological deficit (WED), the size and depth of WEF, but also further evaluate the performance of WEF in terms of fairness and decoupling. Then, the framework was applied to examine WRS in Xinjiang, China from 2004 to 2018. The results indicated that: (1) The production sector contributes above 90% of WEF, and the share of WEF generated by ecological environment water is rising; (2) the increasing trend in WED implies that WRS is deteriorating; (3) GDP-WEF was at an extremely unfair level as the less economically developed cities of the South occupy WEF without contributing to the corresponding economic output; (4) from the 10th to the 13th Five-Year Plan, the proportion of strongly decoupled cities rose from 42.9% to 71.4%, with technological factors responsible for the most significant decoupling efforts. These findings offer direct support for improving local human-water relations and promoting the coordination of WRS and socio-economic development. Graphical abstract: Image 1 Highlights: A novel research framework for WRS was developed based on a 3D WEF model. Assessing the performance of WEF in terms of fairness and decoupling efforts. The production sector contributes above 90% of WEF in Xinjiang. Technological factors are responsible for the most significant decoupling efforts. Findings facilitate the coordination of economic and social progress with WRS.